Size‐Controlled Facile Synthesis of Silver Nanoparticles by Chemical Reduction Method and Analysis of Their Antibacterial Performance. Issue 36 (23rd September 2021) - Halder, Sanjoy; Ahmed, Aninda N.; Gafur, Md. A.; Seong, Gimyeong; Hossain, Muhammad Z.
Abstract: This article aimed at the size‐controlled one‐pot facile synthesis of silver nanoparticles (AgNPs) by chemical reduction method and their antibacterial response against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) bacteria. AgNPs coated with and without trisodium citrate (TSC) were synthesized using silver nitrate as a precursor and hydrazine as a reducing agent. Spherical AgNPs (average size 35 nm) formation, capping agents attachment, and product purity was confirmed by ultraviolet‐visible (UV–vis) spectroscopy, X‐ray diffraction (XRD), field emission scanning microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared (FTIR), the thermogravimetric analysis (TGA), and energy‐dispersive X‐ray (EDX) spectroscopy. Exposing the synthesized TSC uncoated and coated AgNPs to Gram‐negative E. coli bacteria at a concentration of 50 mg L −1, the zone inhibition was found to be 5 mm and 6 mm, respectively. Again, TSC coated AgNPs exhibited a notable zone inhibition of 8 mm to Gram‐positive S. aureus . These results suggest that chemically synthesized TSC coated AgNPs could be used as an antibiotic against S. aureus and E. coli, which is very inspiring. Abstract : TSC coated and uncoated AgNPs were synthesized chemically using silver nitrate precursor, and their antibacterial efficacy was evaluated. TSC capping compounds suppress particle growth, allowing AgNPs to be controlled in size within 35 nm. Without TSC coating, however, particle size increases. On E. coli, TSC coated smaller‐sized AgNPs show more zone inhibition than uncoated AgNPs. Therefore, the surface coating of AgNPs is important for particle size management and increased antibacterial activity.